Altered emotional decision-making in prisoners with borderline personality disorder. - Kirkpatrick, T; Joyce, E; Milton, J; Duggan, C; Tyrer, P; Rogers, R (2007)
Previous studies have identified neuropsychological deficits in individuals with antisocial personality disorder and/or psychopathy. Few studies have examined neuropsychological functioning in individuals with borderline personality disorder (BPD), and no studies have yet investigated cognitive and emotional function in male prisoners with BPD. In this study, we compared the risky decision-making of 17 participants with a history of serious violent or sexual offenses and a diagnosis of DSM-IV BPD with that of 17 participants with similar offending histories but personality disorders other than BPD. Those with BPD exhibited altered processing of information about potential losses (punishment) when the probability of gains (reward) was high; they also increased their choice of risky options even in circumstances where this was clearly avoidable. These data suggest that individuals with a diagnosis of BPD and a history of serious offenses have problems integrating different reinforcement signals when choosing between risky actions, perhaps reflecting corticolimbic dysfunction as an underlying mechanism in BPD.